Epidemiology and risk factors for pneumonia severity and mortality in Bangladeshi children <5 years of age before 10-valent pneumococcal conjugate vaccine introduction. (December 2016) - Saha, Shampa; Hasan, Md; Kim, Lindsay; Farrar, Jennifer; Hossain, Belal; Islam, Maksuda; Ahmed, ASM; Amin, M.; Hanif, Mohammed; Hussain, Manzoor; El-Arifeen, Shams; Whitney, Cynthia; et al.
Abstract Background Pneumonia is the leading infectious cause of morbidity and mortality in young children in Bangladesh. We present the epidemiology of pneumonia in Bangladeshi children <5 years before 10-valent pneumococcal conjugate vaccine introduction and investigate factors associated with disease severity and mortality. Methods Children aged 2–59 months admitted to three Bangladeshi hospitals with pneumonia (i.e., cough or difficulty breathing and age-specific tachypnea without danger signs) or severe pneumonia (i.e., cough or difficulty breathing and ≥1 danger signs) were included. Demographic, clinical, laboratory, and vaccine history data were collected. We assessed associations between characteristics and pneumonia severity and mortality using multivariable logistic regression. Results Among 3639 Bangladeshi children with pneumonia, 61% had severe disease, and 2% died. Factors independently associated with severe pneumonia included ages 2–5 months (adjusted odds ratio [aOR] 1.60 [95% CI: 1.26–2.01]) and 6–11 months (aOR 1.31 [1.10–1.56]) relative to 12–59 months, low weight for age (aOR 1.22 [1.04–1.42]), unsafe drinking water source (aOR 2.00 [1.50–2.69]), higher paternal education (aOR 1.34 [1.15–1.57]), higher maternal education (aOR 0.74 [0.64–0.87]), and being fully vaccinated for age with pentavalent vaccination (aOR 0.64 [0.51–0.82]). Increased risk of pneumonia mortality was associated with age <12 months, low weight for age, unsafe drinking water source, lower paternal education, disease severity, and having ≥1 co-morbid condition. Conclusions Modifiable factors for severe pneumonia and mortality included low weight for age and access to safe drinking water. Improving vaccination status could decrease disease severity.